Insight into the changes of European agriculture during the age of Baroque and enlightenment: Interdisciplinary survey of manor farmyard Švamberk (Czech Republic) - Vobejda, Libor; Šálková, Tereza; Erban Kochergina, Yulia V; Altman, Jan; Thomová, Zuzana (Heliyon, 2024)
Following European exploration of the Americas in the late 15th century, new plants rapidly spread across Europe. Simultaneously, plants from Asia and Africa arrived. Initially, they were grown in ornamental gardens but later became integral to major production centres, significantly transforming European agriculture. Neophytes gained prominence during a period of rapid economic progress in central Europe, and many have been cultivated since the 17th century. Their importance is documented through written sources and archaeobotanical findings. This study of the manor farm Švamberk (Czechia) highlights how multidisciplinary research of agricultural production centres is crucial for understanding pre-industrial landscapes and the environmental impact of early modern societies. Agriculture's development correlates with changes in a landscape now suppressed by industrial interventions, yet key to sustainable development. Plant remains in vault infills and roofs at Švamberk farmstead were dated using dendrochronology, with 99 samples and 81,892 plant macroremains analysed. Dendrochronological and strontium isotope analyses trace forestry and timber trade over time. Timber felled in the 17th century was likely local, but by the late 18th century, timber came via complex transportation from southern Bohemia. Primary crops were grains, oilseeds, and vegetables, with evidence of exotic species like maize, tobacco, sunflowers (native to the Americas), sorghum (native to Africa), Parthenocissus, and Chinese thuja (native to Asia), some of the oldest archaeological evidence of their cultivation in central Europe.
Keywords: Dendroprovenance; Agriculture; Post medieval archaeology; Vault infills; Dendrochronology; Neophytes; Landscape; Archaeootany